Epistemic Orientation for the Technological Future. Toward a Research Agenda for Dealing with Social Challenges of Internet of Things - Amaturo, Enrica; Aragona, Biagio; Felaco, Cristiano (Italian Sociological Review, 2022)
This paper offers an epistemological and theoretical framework, and a research agenda, to face the main ethical and social pitfalls of the deployment of big data and IoT in social domains (SIoT). We rely on the concept of critical optimism to explain epistemic orientation about the technological future, paying particular attention to the social challenges. The framework drives the creation of an agenda for social researchers that aids to detect more evidence on the SIoT opportunities.